Pengaruh Pola Kemitraan Perkebunan Kelapa Sawit Terhadap Pendapatan Petani di Kabupaten Bengkayang - Esidorus, Esidorus; Suyatno, Adi; Kurniati, Dewi (Jurnal Social Economic of Agriculture, 2025)
Palm oil plays a strategic role in Indonesia"™s economy; however, smallholder farmers still face various challenges, such as limited capital, market access, and technological innovation. To address these issues, the government has implemented a partnership system with large companies to enhance farmers' productivity. In Bengkayang Regency, the implementation of such partnerships faces obstacles, particularly land conflicts, administrative boundary issues, and suboptimal profit-sharing mechanisms, which impact farmers' welfare. This study aims to analyze the partnership models in palm oil plantations in Bengkayang Regency, evaluate their influence on farmers' production levels, and examine their impact on farmers' income. The research employs descriptive analysis, income analysis, and a Paired Sample t-test. The findings indicate that the nucleus-plasma partnership model is more beneficial for farmers compared to the profit-sharing model in terms of mechanism and cooperation effectiveness. Statistical tests confirm a significant difference in income between farmers adopting the nucleus-plasma model and those under the profit-sharing scheme. Factors contributing to these income disparities include the production-sharing system, company-owned plantations, farm size, cooperative membership, and cooperative management systems